Digital innovation and entrepreneurship: A review of challenges in competitive markets - Christoph Kreiterling (Journal of Innovation and Entrepreneurship, 2023)
This article presents a narrative review of seven selected studies investigating the impact of digital innovation on entrepreneurship and its outcomes within diverse sociopolitical contexts. Results show that improved innovation output scores and the ability to absorb innovative models are associated with higher GDP growth rates. Technological changes account for 35-40% of the dynamics, while regional factors account for 40%. Internet usage has led to decreased operational costs, increased sales, and better customer interaction for 88% of companies, enabling 83% to expand their markets and 78% to engage more effectively with suppliers. Digitalization fosters entrepreneurship expansion into new markets, creating a positive feedback loop between the two variables. Additionally, the study found that government roles have a more significant influence on entrepreneurship sustainability compared to electronic readiness. Digital technologies have been shown to enhance firm productivity, particularly in manufacturing and intensive industries.
Keywords: 650; Innovation; Entrepreneurship; Regulation; Digitalization; Digital innovation